2018
DOI: 10.1016/j.artd.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval analysis of a failed synthetic mesh extensor mechanism reconstruction after total knee arthroplasty

Abstract: Extensor mechanism disruption after total knee arthroplasty is a relatively rare but potentially devastating complication. One technique to address this problem involves reconstruction with synthetic mesh. Although there are reports of successful clinical outcomes using this technique, we are not aware of any histological analyses of removed mesh grafts. This case report of a failed mesh reconstruction includes a retrieval analysis demonstrating robust host soft-tissue incorporation into the mesh graft and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Expectedly, there were increased rates of mesh revision with longer-term follow-up; however, these results represent a substantial improvement in terms of construct durability when compared with previously described reconstructive techniques 2,11 . Overall, these results support the index hypotheses posed by Browne and Hanssen 6 that the ingrowth of mature, fibrous host tissue into the mesh 23 , as well as increased tensile strength relative to allograft tissue, may afford greater longevity following extensor mechanism reconstruction.…”
Section: Discussionsupporting
confidence: 83%
“…Expectedly, there were increased rates of mesh revision with longer-term follow-up; however, these results represent a substantial improvement in terms of construct durability when compared with previously described reconstructive techniques 2,11 . Overall, these results support the index hypotheses posed by Browne and Hanssen 6 that the ingrowth of mature, fibrous host tissue into the mesh 23 , as well as increased tensile strength relative to allograft tissue, may afford greater longevity following extensor mechanism reconstruction.…”
Section: Discussionsupporting
confidence: 83%
“…A TKA retrieval study demonstrated similar histological findings [29]. The use of mesh in this technique is technically uncomplicated and affordable, and polypropylene mesh has favorable biomechanical properties [13,29]. As such, there is growing interest in its use in the traditionally tenuous reconstruction of relatively devitalized post-TKA extensor mechanism ruptures [10,21,30,31].…”
Section: Discussionmentioning
confidence: 79%
“…Monofilament mesh is well-studied in general surgical hernia repairs 26 and functions by inciting a robust inflammatory fibrotic reaction that promotes host/graft integration [27,28]. A TKA retrieval study demonstrated similar histological findings [29]. The use of mesh in this technique is technically uncomplicated and affordable, and polypropylene mesh has favorable biomechanical properties [13,29].…”
Section: Discussionmentioning
confidence: 99%